Meningkatkan Kesadaran Masyarakat dalam Membuang Sampah Pada Tempatnya dengan Memanfaatkan Tanaman Bambu di Desa Jago Bayo - Rohmah, Adinda Syifa’u; Padila, Julia Dwi; Edward, Fahmi Yohari; Begum, An Najwa Khariunnisa; Darmawan, M. Diaz Shandy; Sinambela, Alhadid Putra; Rahmayanti, Dea Putri; Ardiansah, Reli; Akbar, M. Rizky; Manik, Dina Meitamara; Masrsabella, Cendy; Siregar, Rosi L. Vini (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Awareness and knowledge about clean and healthy living free of waste is very important for people both in cities and villages. In Jago Bayo Village, public awareness of maintaining environmental cleanliness is still low, characterized by the large amount of garbage scattered on the banks of the river and the lack of trash bins at home and in public places. The work program of Group 20 KKNT Period 102 aims to increase community knowledge and awareness about the importance of disposing of waste in its place and teach how to make bamboo-based trash bins. This activity includes making trash bins by utilizing materials available in nature, namely bamboo, and placing the bins in places that are easily accessible to the community. The result of this work program is to increase community awareness in disposing of garbage in its place and increase community skills in making bamboo bins.